AGROTECHNOLOGY OF HIGH-YIELD AND HIGH-QUALITY FIBER CULTIVATION OF FINE-FIBER COTTON VARIETY “SURKHAN-16” - B. Ch. Juraev; O. Sh. Boynazarov; J. B. Juraev (Galaxy International Interdisciplinary Research Journal, 2021)
The new fine-grained cotton variety “Surkhan-16” was selected from the hybrid combination (9871-I x Karshi-6) x (T-5689 x Surkhan-6) at the Uzbek Research Institute of Cotton breeding,seed production and agrotechnology. Authors of the variety: M.Iksanov, B.Ch.Juraev and others This variety has undergone extensive production testing since 2006 in the state varietal testing industries. Elite seeds of new cotton varieties are being propagated in the “Surkhan experimental plot”.